Strengthening National Identity: A Strategy for Reducing and Preventing Migration (Salam International Academic Journal, 2025)
Displacement, migration, and asylum-seeking have been lived experiences for millions of Afghans throughout the country’s history, positioning Afghanistan as one of the world’s leading migrant-sending nations. These phenomena represent some of the most complex and challenging issues facing the country over the past four decades. In light of this, identifying and implementing strategies to reduce migration and facilitate the return of migrants is essential.The present study aims to examine the role of strengthening national identity in reducing migration. The research adopts a descriptive-analytical approach and is based on a literature review. For data collection, relevant scholarly articles were first gathered, from which the most pertinent were selected. The variables of national identity and migration were then analyzed and examined in depth.The findings indicate that individuals with a strong sense of national identity express pride in their national community and in the elements that shape it, such as shared history, religion, and culture, and distinguish themselves from others based on these elements. Accordingly, strengthening national identity can significantly reduce the inclination toward migration and contribute to the return of Afghan migrants.
Keywords: National Identity; Political Identity; Personal Identity; Ethnic Identity; Migration